Editorial. (January 2015) - Mansfield-Devine, Steve
Abstract : The major breach of Sony Pictures' networks has inevitably led to multifarious repercussions. And one of the most interesting has not been against the firm itself (although it is being sued for its allegedly lousy security) but against media outlets reporting the story.